Pengaruh Beban Kerja Burnout dan Konflik Kerja terhadap Stres Kerja Karyawan PT DM Baru Retailindo - Tatik Dwi Wahyuni; Prayekti Prayekti; Didik Subiyanto (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this study was to determine the effect of workload, burnout, and work conflict partially on the work stress of employees. The population in this study were employees of PT DM Baru Retailindo, precisely at the DM Baru 6 Bantul branch. Data was collected through a questionnaire and then analyzed using multiple linear regression with the help of the SPSS software application version 25.0. Based on the results of research tests found, namely: (1) Workload has a positive and significant effect on Employee Work Stress. (2) Burnout has a positive and significant effect on Employee Work Stress. (3) Work Conflict has a positive and significant effect on Employee Work Stress. (4) Workload, Burnout, and Work Conflict have a positive and significant effect on Employee Work Stress. Keywords: Workload, Burnout, Work Conflict, Employee Work Stress.